Swaziland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper describes recent economic developments in Swaziland and discusses some of the key issues that have a bearing on the economic outlook and policy debate. The paper examines developments with regard to output and inflation, fiscal policy, monetary policy and financial markets, and the external sector. It elaborates the economic impact of HIV/AIDS. The sources of GDP growth and the outlook are analyzed. The paper also examines the issue of external competitiveness, and describes the finances of the Public Service Pensions Fund.